Aid diversion, accountability and questions unanswered: contextualising the World Bank working paper on offshore capture of foreign aid. Issue 3 (23rd November 2020) - Damianos, Stephen
Abstract : Purpose: The purpose of this paper is to engage a contentious World Bank publication beyond its controversy. In particular, it assesses mechanisms that facilitate elite capture of foreign aid and potential strategies of accountability. Design/methodology/approach: This paper adopts desk research methodology, relying primarily upon journal papers, books and internet sources related to international development and corruption. Findings: This paper isolates three factors that contribute to elite capture of foreign aid: the codified secrecy of offshore tax havens, customary clientelism and decentralised aid. Regarding accountability measures, it advocates decreasing livelihood dependence on local elites and encouraging meaningful involvement by civil society. Originality/value: This paper de-sensationalises the controversial World Bank working paper, providing a contextualised reading that at the time of publication does not yet exist.